The effect of hybrid anti-stripping agent with polymer on the moisture resistance of hot-mix asphalt mixtures. Issue 1 (1st January 2019) - Abed, Alaa H.; Qasim, Zaynab I.; Al-Mosawe, Hasan; Norri, Hussein H.
Abstract: Asphalt mixtures exhibit deterioration in properties due to several factors; one of these factors is the moisture damage. Many kinds of research have focused on this matter in Iraq; however, up to now, the pavement is suffering from moisture failure due to the penetration of surface water. Asphalt concrete is modified in this research by adding anti-stripping agent and polymer to withstand the moisture damage that occurs in the pavements. Key factors to enhance the mixtures to withstand the damages due to moisture are aggregate–binder cohesion and adhesion. Therefore, the aim of this research is to evaluate the effect of the addition of the anti-stripping agent and the polymer on the moisture susceptibility of asphalt concrete mixtures before and after conditioning. Indirect tensile strength test, Marshall test, and double punching shear test are used to satisfy the evaluation of the mixture properties. The anti-stripping agents that are used were WetFix with styrene butadiene styrene (SBS) polymer with different percentages. It is found that the modified asphalt mixture has good mixture properties in terms of Marshall stability, retained Marshall stability, and better resistance of moisture and stripping. It has been found that the addition of 0.5% WetFix and 3% SBS polymer maximizes the properties among other percentages. It is also observed that the mixing technique of modifiers is important to the resulting performance of asphalt mixtures.